Picosecond molecular motions in bacteriorhodopsin from neutron scattering. - Fitter, J (1997)
The characteristics of internal molecular motions of bacteriorhodopsin in the purple membrane have been studied by quasielastic incoherent neutron scattering. Because of the quasihomogeneous distribution of hydrogen atoms in biological molecules, this technique enables one to study a wide variety of intramolecular motions, especially those occurring in the picosecond to nanosecond time scale. We performed measurements at different energy resolutions with samples at various hydration levels within a temperature range of 10-300 K. The analysis of the data revealed a dynamical transition at temperatures Td between 180 K and 220 K for all motions resolved at time scales ranging from 0.1 to a few hundred picoseconds. Whereas below Td the motions are purely vibrational, they are predominantly diffusive above Td, characterized by an enormously broad distribution of correlation times. The variation of the hydration level, on the other hand, mainly affects motions slower than a few picoseconds.